2004
DOI: 10.1101/gad.1201204
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA silencing suppressors inhibit the microRNA pathway at an intermediate step

Abstract: RNA silencing suppressors from different plant viruses are structurally diverse. In addition to inhibiting the antiviral silencing response to condition susceptibility, many suppressors are pathogenicity factors that cause disease or developmental abnormalities. Here, unrelated suppressors from multiple viruses were shown to inhibit microRNA (miRNA) activities and trigger an overlapping series of severe developmental defects in transgenic Arabidopsis thaliana. This suggests that interference with miRNA-directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
501
6
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(563 citation statements)
references
References 50 publications
25
501
6
24
Order By: Relevance
“…To test this possibility, we examined the effects of several well-characterized viral silencing suppressors, which can interfere with siRNA production from dsRNA precursor, on srPSTVd accumulation. The coat protein of turnip crinkle virus has been shown to selectively inhibit the production of siRNAs (16,18,24,70) but have little effect on the production of miRNAs in plants (16,24). P19 from tomato bushy stunt virus and P1/HC-Pro from tobacco etch virus were shown to affect siRNA accumulation in some systems (P19 [35,70,80] and HC-Pro [24,35,52,54]).…”
Section: Resultsmentioning
confidence: 99%
“…To test this possibility, we examined the effects of several well-characterized viral silencing suppressors, which can interfere with siRNA production from dsRNA precursor, on srPSTVd accumulation. The coat protein of turnip crinkle virus has been shown to selectively inhibit the production of siRNAs (16,18,24,70) but have little effect on the production of miRNAs in plants (16,24). P19 from tomato bushy stunt virus and P1/HC-Pro from tobacco etch virus were shown to affect siRNA accumulation in some systems (P19 [35,70,80] and HC-Pro [24,35,52,54]).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have identified several miRNAs in rice that are up-regulated in response to Tungro virus infection (N. Sanan-Mishra unpublished results). Viral suppressors of gene silencing like HC-Pro, p19, p21, and p69 are important pathogenicity factors that help in disease symptom appearance and various developmental abnormalities in infected plants (Chapman et al, 2004). Several studies have shown that these suppressors are involved in the regulation of miRNA activities (Kasschau et al, 2003;Chen et al, 2004;Chapman et al, 2004).…”
Section: Functions Of Micro Rnamentioning
confidence: 99%
“…Viral suppressors of gene silencing like HC-Pro, p19, p21, and p69 are important pathogenicity factors that help in disease symptom appearance and various developmental abnormalities in infected plants (Chapman et al, 2004). Several studies have shown that these suppressors are involved in the regulation of miRNA activities (Kasschau et al, 2003;Chen et al, 2004;Chapman et al, 2004). HC-Pro inhibited the expression level and activity of miR171, and caused developmental deficiency (Kasschau et al, 2003).…”
Section: Functions Of Micro Rnamentioning
confidence: 99%
“…Several studies demonstrated that transgenic expression of VSRs leads to the alteration of miRNA accumulation and, consequently, numerous developmental abnormalities are produced (Kasschau et al, 2003;Chapman et al, 2004). These alterations underlie many disease symptoms typically observed during plant viral infections (Siddiqui et al, 2008;Bazzini et al, 2011;Shimura and Pantaleo, 2011).…”
Section: Effects Of Tmv Replicase Proteinmentioning
confidence: 99%